The Use of Metal Nanoparticles as an Antimicrobial Agent and as a Catalyst for Organic Synthesis - Marina, Nancy (Université d'Ottawa / University of Ottawa, 2018)
Nanomaterial’s applications have expanded greatly in the last few decades due to their interesting properties. Example of nanomaterials are metal nanoparticles NP. NP have interesting physical and optical properties that make them different and more useful than their bulk counterpart. Some of these properties are the large surface area to mass ratio and their ability to absorb light. NP have been applied in the health, environment, and catalysis fields The main focus of this thesis will be on the applications of nanomaterials in medicine and catalysis. In the first part of the thesis, coated polydispersed and polymorphic silver nanostructures AgNS were synthesized using seed mediated method. The synthesized AgNS were characterized using SEM, TEM, and UV-VIS. The stability of these AgNS were determined by measuring the shift in the plasmon band over time and by measuring their zeta potential. Moreover, the bactericidal properties of coated AgNS were tested on gram negative bacteria such as Escherichia coli and Pseudomonas aeruginosa and gram positive bacteria such as Methicillin- Resistant Staphylococcus aureus (MRSA) and Staphylococcus aureus. The second part of the thesis discusses the field of nanocatalysis where different supported metal nanoparticles on TiO2 were synthesized and characterized by TEM, diffuse reflectance DR, XPS and ICP. The activity of the synthesized catalysts was tested for Ullmann C-C cross coupling reaction. The use of the photoresponisve Pd@TiO2 under the combination of UVA 368 and visible light 465nm irradiation offered the highest selectivity toward the cross coupling product.
Keywords: Nanomaterials; Photocatalysis; Antimicrobial